VALUE-ADDED TAX INCREASE AND HOUSEHOLD CONSUMPTION IN INDONESIA: BALANCING FISCAL SUSTAINABILITY AND CONSUMER WELFARE - Isnaila Fentiana Alfitriyeni; Eka Vaulana Rhodhiska Wulandari (Universitas Tulungagung, 2025)
Value Added Tax (VAT) serves as one of Indonesia's primary sources of government revenue and plays a crucial role in supporting fiscal sustainability. The implementation of the 12% VAT rate in 2025 has generated considerable debate regarding its potential effects on household purchasing power and economic welfare. Although previous studies have examined either the macroeconomic consequences of VAT adjustments or tax administration, limited research has integrated the legal framework, tax collection mechanism, and socioeconomic implications of the new VAT policy within a comprehensive analytical framework. This study aims to examine the implementation of Indonesia's 12% VAT policy, analyze its impact on household consumption and government revenue, evaluate its effectiveness in balancing fiscal sustainability and tax equity, and propose policy recommendations. A qualitative descriptive approach was employed using documentary analysis and a literature review. The study utilized secondary data derived from government regulations, academic publications, official reports, and credible national and international economic sources. Data were analyzed through content analysis and comparative descriptive analysis to assess the relationship between VAT policy, consumer behavior, tax administration, and fiscal outcomes. The findings indicate that the VAT increase strengthens government revenue and supports fiscal sustainability; however, it also reduces household purchasing power, particularly among lower-income groups, and creates short-term inflationary pressures. The effectiveness of the policy depends on efficient tax administration, transparent implementation of the self-assessment system, and complementary fiscal measures, including targeted social assistance and tax exemptions for essential goods. This study contributes to the literature by providing an integrated perspective on VAT reform and offers practical insights for designing equitable and sustainable fiscal policies in Indonesia.